2007
DOI: 10.1111/j.1537-2995.2007.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of blood irradiation with a teletherapy unit: damage to stored red blood cells after cobalt‐60 gamma irradiation

Abstract: The method used to store the blood bags during irradiation guaranteed that all damage caused to the cells was exclusively due to the action of radiation at the doses applied. It was demonstrated that prolonged storage of 60Co-irradiated RBCs results in loss of membrane phospholipids asymmetry, exposing phosphatidylserine (PS) on the cells' surface with a time and dose dependence, which can reduce the in vivo recovery of these cells. A time- and dose-dependence effect on the extracellular K+ and plasma-free Hb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
2
5
0
3
Order By: Relevance
“…These data are consistent with other findings that irradiation (with a dose lower than in our study; 25 Gy), filtration, and combined irradiation and filtration before storage can cause significant damage in RBCs and intensify the RBC storage lesions such as increased free Hb and K + [31]. Similar to our results, the increase in free Hb plasma levels in the irradiated RBC units (30 Gy) was found less evident during the first days of storage [7]. …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These data are consistent with other findings that irradiation (with a dose lower than in our study; 25 Gy), filtration, and combined irradiation and filtration before storage can cause significant damage in RBCs and intensify the RBC storage lesions such as increased free Hb and K + [31]. Similar to our results, the increase in free Hb plasma levels in the irradiated RBC units (30 Gy) was found less evident during the first days of storage [7]. …”
Section: Discussionsupporting
confidence: 83%
“…In consistence with our results, it was demonstrated that prolonged storage (up to 45 days) of the RBCs irradiated with a cobalt teletherapy unit (30 and 40 Gy) resulted in loss of membrane phospholipid asymmetry, exposing PS on the cells' surface in a time- and dose-dependent manner. The magnitude of this effect did not seem to be clinically relevant [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, identical concentrations of both antioxidants were applied. Hemolysis, and the protection by antioxidants was more evident at day 20 which is consistent with findings reported by others [30,31]. At concentrations up to 3.125 mmol/l, Trolox was somewhat more effective than mannitol in protecting against progressive hemolysis.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the finding by Leitner and coworkers of critically enhanced in vitro hemolysis in stored irradiated units probably resembles the well‐known enhancement of the in vitro hemolysis rate in underfilled components 24 . Other reports on quality control of blood irradiation also divided RBC units into unusually small aliquots, which do not resemble the normal filling status of RBCs to study differences between groups without the bias of biologic variabilities 25 …”
Section: Discussionmentioning
confidence: 89%